2013
DOI: 10.1007/s00408-013-9487-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Cost Analysis of Exacerbations in Chronic Obstructive Pulmonary Disease

Abstract: Antibiotic treatment of our population was in compliance with local guidelines. The rate of failure observed in our study was lower than that reported in previous studies; however, the small percentage of patients that required hospital attention generated almost two-thirds of the total costs of the exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…They are associated with increased health care costs [31] and significant impairment in HRQoL of patients [32], and in our study showed a strong association with the presence of depressive symptoms. Moreover, a large followup study has found an increased risk of exacerbations (adjusted incidence rate ratio (IRR), 1.51; 95% confidence interval (CI), 1.01e2.24) and hospitalizations (adjusted IRR, 1.72; 95%CI, 1.04e2.85) in patients with probable depression identified by HADs (Hospital Anxiety and Depression) scores !11, compared with patients without depression [7].…”
Section: Discussionmentioning
confidence: 53%
“…They are associated with increased health care costs [31] and significant impairment in HRQoL of patients [32], and in our study showed a strong association with the presence of depressive symptoms. Moreover, a large followup study has found an increased risk of exacerbations (adjusted incidence rate ratio (IRR), 1.51; 95% confidence interval (CI), 1.01e2.24) and hospitalizations (adjusted IRR, 1.72; 95%CI, 1.04e2.85) in patients with probable depression identified by HADs (Hospital Anxiety and Depression) scores !11, compared with patients without depression [7].…”
Section: Discussionmentioning
confidence: 53%
“…Antibiotic therapy in patients with previous severe exacerbations is one of the key factors in promoting further Aspergillus species isolation. In a recent study conducted in Spain, approximately 73% of COPD patients received antibiotics [31]. …”
Section: Discussionmentioning
confidence: 99%
“…isolation. In fact, in a recent publication, it was found that almost 73% of COPD patients in Spain presenting with a Type I Anthonisen exacerbation received antibiotics [27]. Prospective studies focusing on this specific population are much needed to determine whether Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%